REVIEWING THE ROLE OF PARENTS IN ELEMENTARY SCHOOL STUDENTS' LEARNING IN THE PANDEMIC ERA - Arif Widodo; Prayogi Dwina Angga; Muhammad Syazali; Umar Umar (JURNAL EDUSCIENCE, 2023)
One of the consequences of limiting face-to-face learning in the pandemic era is the implementation of distance learning. At the elementary school level, the application of distance learning is carried out in various ways, one of which is by applying online learning. This article aims to analyze how important the role of parents in learning for elementary school-aged children is in the pandemic era. This research method uses a literature study approach. Data was collected by browsing research articles through Google Scholar. The article analyzed is a research article that discusses the involvement of parents in distance learning in the pandemic era. The results of the analysis of various kinds of literature show how important the role of parents in supporting the online learning process is. In online learning, the learning process cannot run optimally without collaboration between teachers and parents. Most of the teacher's tasks in online learning have been taken over by parents. Parents function as facilitators, motivators, and become the main guides in the learning process. Another role that is no less important than parents is as a learning supervisor, through this supervision control of the quality of learning can be carried out even though it is constrained by distance from the schoolKeywords: online learning, learning quality, parental involvementÂ AbstrakSalah satu akibat dari terbatasnya pembelajaran tatap muka di era pandemi adalah penerapan pembelajaran jarak jauh. Di tingkat sekolah dasar, penerapan pembelajaran jarak jauh dilakukan dengan berbagai cara, salah satunya dengan menerapkan pembelajaran daring. Artikel ini bertujuan untuk menganalisis seberapa penting peran orang tua dalam pembelajaran bagi anak usia sekolah dasar di era pandemi. Metode penelitian ini menggunakan pendekatan studi literatur. Data dikumpulkan dengan menelusuri artikel penelitian melalui Google Scholar. Artikel yang dianalisis merupakan artikel penelitian yang membahas tentang keterlibatan orang tua dalam pembelajaran jarak jauh di era pandemi. Hasil analisis berbagai literatur menunjukkan betapa pentingnya peran orang tua dalam mendukung proses pembelajaran daring. Dalam pembelajaran daring, proses pembelajaran tidak dapat berjalan maksimal tanpa adanya kerjasama antara guru dan orang tua. Sebagian besar tugas guru dalam pembelajaran daring sudah diambil alih oleh orang tua. Orang tua berfungsi sebagai fasilitator, motivator, dan menjadi pemandu utama dalam proses pembelajaran. Peran lain yang tidak kalah penting dari orang tua adalah sebagai pengawas pembelajaran, melalui pengawasan ini dapat dilakukan pengendalian mutu pembelajaran meskipun terkendala jarak dengan sekolah.Kata kunci: pembelajaran online, kualitas pembelajaran, keterlibatan orang tua